Gorszyciele wszystkich epok, łączcie się! Manifest na początek wieku - Ojcewicz, Grzegorz (Acta Polono-Ruthenica, 2006)
The article focuses on the influence which shockers - rebels and scandalizers - wield on the fate of the world. It unveils some universal receptivity mechanisms corresponding to activities taken by radicals, whose uncompromising attitude and views were of epoch-making importance in the development of culture. I compare my reflections first of all with the field of verbal art, which does not mean however that they are not proved correct in some other domains. Knowledge of those mechanisms allows one to precisely predict phases of every new rebellion, essential from the standpoint of both the thought revolution, and importance of a rebel for breaking dogmas and creating new values, principles and ideals. At the same time, the knowledge proves that every opposition to culture has its sources, course and end, with the last one usually initiating another duel of an unyielding individual against norms imposed on him/her not only by some abstract thousand-year-old tradition, but also by some definite people shaping the contemporary morality, i.e. politicians, lawyers and clergymen.